The Recent Introduction of a Freshwater Asiatic Bivalve, Limnoperna forlunei (Mytilidae) into South America - Darrigran, Gustavo Alberto (1995)
The temporal and spatial distribution of Limnoperna forlunei in the Argentine littoral of the Rio de la Plata is reported. Its distribution is limited by the most contaminated area and by an increment in the saline concentration. A decrease in density was recorded between August 1992 and January 1993. Subsequently there was an increase in density up to a maximum of 82,000 ind-m-2 in May 1993. It is concluded that because of its functional and morphological characteristics. L. fortuna will spread quickly. With Corbicuia fluminea and C. largitherti, Limnoperma fortunei is the third invading species to be introduced into South America from Southeast Asia. Its possible entry into Argentina, by trading ships from Korea and Hong Kong, is suggested. Import peaks correspond with the estimated arrival of these three invaders.